Overcoming neoliberal globalization: social-ecological transformation from a Polanyian perspective and beyond - Brand, Ulrich; Görg, Christoph; Wissen, Markus (Globalizations, 2020)
The ecological crisis has intensified in many respects. Prominent proposals to deal with the crisis are discussed under the header 'sustainability transformations' or even 'Great Transformation'. We argue that most contributions suffer from a narrow analytical approach to transformation ignoring the largely unsustainable dynamics of global capitalism and the power relations involved in it. Thus, a 'new critical orthodoxy' of knowledge about transformation is emerging which runs the danger to contribute to a spatially and socially highly uneven green capitalism. This article claims that the current debate on social-ecological transformation can be enriched by a Polanyian understanding but also based on regulation theory. We distinguish between three types of transformation: incremental adaptation of the current institutional systems, institutional change in favour of a new 'green' phase of capitalism, and a post-capitalist great transformation that implies a profound structural change of the mode of production and living.
Keywords: POLANYI, Karl, 1886-1964; capitalism; crises; debates & debating; ecological crisis; globalization; imperial mode of living; nature as fictitious commodity; regulation theory; social ecology; social-ecological transformation; sustainability

Ecology, Democracy, and COVID-19: Rereading and radicalizing Karl Polanyi - Ryan, J. Michael (COVID-19: Volume I: Global Pandemic, Societal Responses, Ideological Solutions, 2020)
The SARS-CoV-2 virus, and the associated COVID-19 pandemic, is perhaps the greatest threat to life, and lifestyles, the world has known in more than a century. The scholarship included here provides critical insights into the ethics and ideologies, inequalities, and changed social understandings that lie at the heart of this pandemic. This volume maps out the ways in which the pandemic has impacted (most often disproportionately) societies, the successes and failures of means used to combat the virus, and the considerations and future possibilities – both positive and negative – that lie ahead. While the pandemic has brought humanity together in some noteworthy ways, it has also laid bare many of the systemic inequalities that lie at the foundation of our global society. This volume is a significant step toward better understanding these impacts. The work presented here represents a remarkable diversity and quality of impassioned scholarship and is a timely and critical advance in knowledge related to the pandemic. This volume and its companion, COVID-19: Volume II: Social Consequences and Cultural Adaptations, are the result of the collaboration of more than 50 of the leading social scientists from across five continents. The breadth and depth of the scholarship is matched only by the intellectual and global scope of the contributors themselves. The insights presented here have much to offer not just to an understanding of the ongoing world of COVID-19, but also to helping us (re-) build, and better shape, the world beyond.
Keywords: COVID-19; disease & health Issues; health

Karl Polanyi and the Contemporary Political Crisis: Transforming Market Society in the Era of Climate Change - Kirby, Peadar (Bloomsbury Publishing, 2020)
Has politics reached breaking point? Rather than defending liberalism or abandoning it, how can a socially just and ecological alternative be built? Peadar Kirby investigates the causes of our current multifaceted global crisis by drawing on the work of Karl Polanyi. This book explores Polanyi's theory that social disruptions result from the attempt to run society according to the rules of the market. Drawing on these ideas, it outlines pathways towards an alternative future that overcome weaknesses in Marxism. Linking the ecological, political and socio-economic crises, Kirby identifies that an alternative socio-ecological model is emerging, consistent with the insights of Polanyi. Karl Polanyi and the Contemporary Political Crisis is an urgent intervention into key debates on the future of politics, on the low-carbon transition, on automation and on the emerging world order.
Keywords: climate change; ecological crisis

Karl Polanyi on strategy: The effects of culture, morality and double-movements on embedded strategy - Faulconbridge, James R.; Muzio, Daniel (Critical Perspectives on Accounting, 2020)
Karl Polanyi is arguably one of the most significant economic sociologists. At first glance the links between Polanyi’s ideas about markets, society and institutions and strategy may not be obvious. However, there is a hereto unrecognised link between recent writing about institutions and strategy and Polanyi’s work. In this paper we, therefore, chart how, when recognised, these links reveal that Karl Polanyi’s work might provide new ways of thinking about strategy. Our over-riding claim is that Polanyi’s ideas reveal the importance of considering how strategies are defined, responded to, and ultimately rendered effective or ineffective in ways that are determined by relationships between markets, the state and society. It is thus crucial to understand strategy as embedded, this implying consideration of a strategy’s legitimacy in economy and society as an instituted process at any particular place and time. This also implies wider political questions about strategy in society and the extent to which strategists need to be aware of the ‘double movement’ Polanyi discusses and ensure strategies serve the interests of society as well as those of the market.
Keywords: Double movement; Globalization; Law firms; Polanyi; Strategy

A Polanyi-inspired perspective on social-ecological transformations of cities - Bärnthaler, Richard; Novy, Andreas; Stadelmann, Basil (Journal of Urban Affairs, 2020)
Based on a Polanyi-inspired research program, we analyze urban transformations as interrelations between infrastructural configurations, i.e. context-dependent material infrastructures and their multi-scalar political-economic regulations, and socio-cultural modes of living. Describing different modes of infrastructure provisioning in Vienna between 1890 and today, we illustrate how political-economic processes of commodification and decommodification have co-evolved with socio-culturally specific modes of living, grounded in different classes and milieus. We show how, today, two modes of living—“traditional,” established during postwar welfare capitalism, and “liberal,” formed during neoliberal capitalism—co-exist. In the current conjuncture of rising inequality, neoliberal urban regeneration, and accelerating climate crisis, these modes of living are not only increasingly polarized and antagonistic, but also increasingly unable to satisfy needs and self-defined aspirations. Therefore, we explore the potential of social-ecological infrastructural configurations as an alliance-building project for a systemic social-ecological transformation, potentially linking different classes, social segments and forces around a common eco-social endeavor.

Polanyi meets Bolsonaro: Reactionary politics and the double movement in twenty-first-century Brazil - Evans, Peter (International Sociology, 2020)
Twenty-first-century Brazil’s political evolution is a window on the dynamics of contemporary political transitions. The inability of Brazil’s Workers’ Party to sustain its social democratic project and the subsequent rise of the reactionary regime of Jair Bolsonaro are, in turn, part of a global pattern of political change. Karl Polanyi’s vision of the ‘double movement,’ in which the dominance of the market vies with the countervailing movement for social protection, offers an analytical springboard for reflecting on these political transitions. Trying to understand the movement for social protection leads to examining ebbs and flows in the momentum of mobilization. Trying to understand how market dominance leads to reaction brings us back to Polanyi’s advocacy of ‘crass materialism’ as a lens for looking at reaction, and from there to consideration of how the structural power of capital undercuts efforts at social protection and opens the door to reaction.
Keywords: Brasil; Brazil; Brésil; Polanyi; finance; finanzas; protección social; protection sociale; reacción; reaction; réaction; social protection

Re-grounding the city with Polanyi: From urban entrepreneurialism to entrepreneurial municipalism - Thompson, Matthew; Nowak, Vicky; Southern, Alan; Davies, Jackie; Furmedge, Peter (Environment and Planning A: Economy and Space, 2020)
Conventional approaches to local economic development are failing to address deepening polarisation both within and between city regions across advanced capitalist economies. At the same time, austerity urbanism, particularly in the UK, presents challenges for urban authorities facing reduced budgets to meet increased demands on public services. Municipalities are beginning to experiment with creative responses to these crises, such as taking more interventionist and entrepreneurial roles in developing local economies, generating alternative sources of revenue or financialising existing assets. Rooted in a Polanyian perspective and building on the concepts of the entrepreneurial state and grounded city, we identify an embryonic alternative approach – what we call ‘entrepreneurial municipalism’ – as a policy pathway towards resolving enduring socioeconomic problems where neoliberal urban-entrepreneurial strategies have failed. We situate entrepreneurial municipalism as one strand in an assemblage of new municipalist interventions, between radical urban social movements and more neoliberal strategies such as financialised municipal entrepreneurialism. Drawing on original research on the Liverpool City Region, we explore how local authorities are working with social enterprises to harness place-based assets in ways which de-commodify land, labour and capital and re-embed markets back into society. Finally, we draw upon Polanyi as our guide to disentangle differences in approach amongst divergent forms of municipalist statecraft and to critically evaluate entrepreneurial municipalism as a possible trajectory towards the grounded city.
Keywords: Entrepreneurial state; Polanyian economic geography; local economic development; municipal statecraft; urban policy

BRIE Working Paper 2020-6 What Polanyi Teaches Us: The Platform Economy and Structural Change - Eldred, Christopher (The Berkeley Roundtable on the International Economy, 2020)
The welfare system was meant to reduce the 9 vulnerability of citizens to the market, thereby containing the consequences of the market economy and labor commodification. [...] As an adaptation to the consequences of the market, the welfare system is an effort to cushion the effects of the market, not a change its underlying logic of commodification. [...] From this perspective, the political debates about the rules to be applied to the operations of the platform economy are part of the “second movement,” i.e., a reaction to the platform economy. [...] In contrast, to the industrial revolution where the capitalist moved production into the factory to develop greater control than was possible with the putting-out system, the platform extrudes the work and obligations outside the boundaries of the firm. [...] In actuality the relationship between the members of the ecosystem and the platform is hierarchical and based upon an extreme power asymmetry within which the ecosystem members are at the mercy of the platform which controls the nexus of relationships (Cutolo and Kenney, 2020).
Keywords: platform economy; welfare

Pandemic Paradox and Polanyi: Financial Markets Rise, Economies Crash, and Regulators Toss a Coin - Findlay, Mark (2020)
In the pandemic, investors like all responsible citizens share an obligation to keep the community safe. This obligation extends to informed market decision-making which goes beyond self-interest. The current disconnect between financial markets and the economy is a story of two different realities – or perhaps one harsh reality and one expectant gamble. The disconnect cannot just be explained by the different purposes of economic and financial market analysis but rather by the information indicators on which these rely. To forewarn regulators concerned that these two worlds of global wealth generation and growth moving to polar opposite futures, this brief review has these aims:• To reflect on a legal model for financial markets, their regulation and its limitations so that law and finance may be understood as positively relational when considering market sustainability; and then• To suggest that the explanation for this dangerous disconnect can be found in Karl Polanyi’s understanding of fictitious commodities in self-regulating markets, dis-embedding from the social and his propositions for market correction through the double movement.Despite the neoliberal logic to the contrary (where financial markets are deemed only for maximising investor/shareholder profit) financial market regulation should prioritise market sustainability as part of pandemic control policy.
Keywords: disconnect; economy; financial markets; market sustainability and resilience; pandemic crisis; responsible market decision-making

Commodification & countermovement: community-supported agriculture (CSA): a case study in Minas Gerais, Brazil - Matzembacher, Daniele Eckert; Meira, Fabio Bittencourt (Organizações & Sociedade, 2020)
The conventional way of producing and distributing food is based on the use of agrochemicals, fertilizers, industrial fertilizers and other techniques from the Green Revolution, with increasing dependence on financial-industrial capital, which implies the intensification of the agriculture commodification. The object of this study was the emergence of modes of organization resisting this trend. Based on the theoretical reference of Karl Polanyi (2012a, 2012b), a case study was developed in a Community-Supported Agriculture (CSA) initiative. It is a movement that resituates agricultural production through the principles of fair trade, agroecology and the use of short supply chains, which bring production and consumption closer together. The result is a better nutritious quality food at affordable and fair price. The analysis of the CSA Alfa case points to the coexistence of different principles of regulation, in a combination of mercantile exchange and reciprocity. According to the proposition by Karl Polanyi, the economic activity is shown to imbricate with the social aspect, of which friendship, tolerance, fidelity and commitment establish a community ethos around food. The CSA seems to manifest a countermovement to the commodification by enhancing the relative autonomy of individuals that elevates the social cohesion of the participating groups. Resumo A forma que se tornou convencional de produzir e distribuir alimentos baseia-se no uso de agroquímicos, adubos, fertilizantes industriais e de outras técnicas provenientes da Revolução Verde, com crescente dependência do capital financeiro-industrial. Isto significa a intensificação da mercantilização da agricultura. O problema que norteou esta pesquisa é a emergência de modos de organização resistentes a essa tendência. Com base no referencial teórico de Karl Polanyi (2012a, 2012b), construiu-se um estudo de caso cujo objeto é a agricultura sustentada pela comunidade, cujo acrônimo em inglês é CSA (community supported agriculture). Trata-se de um movimento que ressitua a produção agrícola pelos princípios do comércio justo e da agroecologia e uso de cadeias curtas que aproximam produção e consumo. O resultado é um alimento de qualidade nutritiva superior a preço acessível e justo. A análise do caso CSA Alfa aponta a coexistência de diferentes princípios de regulação numa combinação de troca mercantil e reciprocidade. Na esteira de Karl Polanyi, observa-se a atividade econômica imbricada ao social, daí que amizade, tolerância, fidelidade e comprometimento estabelecem um ethos comunitário em torno do alimento. A CSA parece manifestar um contramovimento à mercantilização ao potencializar a autonomia relativa dos indivíduos, o que eleva a coesão social dos grupos participantes.
Keywords: Karl Polanyi; commodification; community-supported agriculture; reciprocity; social cohesion

Transformation or Structural Change? What Polanyi Can Teach Us about the Platform Economy - Kenney, Martin; Zysman, John; Bearson, Dafna (2020)
The rise of the platform economy marks the latest phase in the ongoing digital revolution. Indeed, the platform is to this digital era what the factory was to the industrial era, both a symbol and an organizing mechanism. Gernot Grabher and Jonas König (2020) used Karl Polanyi’s analysis of what he termed the “great transformation” to frame the rise of platform economy. The platform economy is remarkable as it confirms Polanyi’s (and Marx’s before him) insight that the reach of the market is based upon increased commodification as it has been able to reach into ever more parts of social life. We introduced the term “platform economy” in 2015 because we recognized that the digital platforms were changing the dynamics of capitalist accumulation —- an analysis framed by regulationist school of political economy. The intuition was that the socio-technical innovation of digital online platforms was the critical fulcrum for an economic restructuring that would rewire the flows of data and ultimately money and power. The firms we have termed the “mega-platforms”, Apple, Amazon, Facebook, Google, and Microsoft, have become the most valuable and powerful firms in the world. Importantly, the reach of these platforms is global and yet local and personal. Moreover, this platform power has only been reinforced during the COVID-19 pandemic.
Keywords: COVID-19; Great Transformation; Polanyi; platform economy

This freedom kills: Karl Polanyi’s quest for an alternative to the liberal vision of freedom - Brie, Michael (Karl Polanyi and twenty-first-century capitalism, 2020)
The chapter reconstructs the emergence and formulation of Karl Polanyi's central research question: How is responsible freedom possible in a complex modern society? The origins of this question in the time before the First World War and the confrontations with the challenge of neoliberalism and fascism are discussed. It is shown that Karl Polanyi's concept of freedom has four dimensions. Polanyi connects negative, positive, substantial and social freedom with each other and formulates a highly innovative research programme which forms the basis for The Great Transformation and later works.
Keywords: freedom; freedom in a complex society

Commodified money and crustacean nations - Desai, Radhika (Karl Polanyi and twenty-first-century capitalism, 2020)
Though Polanyi referred to three distinct fictitious commodities, one, money, and the fate of the apex structure that commodified it, the gold standard, structured The Great Transformation’s narrative. Despite this centrality of money and its commodification to Polanyi’s masterwork, there is near-deafening silence in Polanyi scholarship on money as a fictitious commodity. This chapter ends it. It traces Polanyi’s understanding of fictitious commodities to its sources in classical political economy and explains how the near total dominance of the antithetical tradition of neoclassical economics obscures understanding. The chapter also argues that the resulting argument shared a great deal with the classical Marxist theories of imperialism and of uneven and combined development of previous decades, particularly their arguments about the centrality of powerful nation states to capitalism. It stresses another hitherto neglected aspect of Polanyi’s argument, that the double movement led to the emergence of ‘crustacean nations’. As such, the chapter argues, The Great Transformation contributes a great deal towards a new approach to understanding world affairs, geopolitical economy, which challenges Ricardian ‘universalist’ understandings and takes the ‘materiality of nations’ seriously. It, and Polanyi, are more relevant than ever in our ‘deglobalizing’ age of multi-polarity.
Keywords: Marxism; fictitious commodities; imperialism; money

Introduction: Karl Polanyi in the twenty-first century - Desai, Radhika (Karl Polanyi and twenty-first-century capitalism, 2020)
This introduction places the contributions that follow in the context of Polanyi’s rising influence, its causes and effects, and of the key twenty-first century developments that make his oeuvre more relevant than ever. It emphasizes how the contributions push the boundaries of received understandings of Polanyi. While some contributions fill gaping holes, such as those on money as a fictitious commodity, others overturn received understandings, whether that of the double movement or fictitious commodities, or the provenance (Central European or American) of his principal ideas and concerns or how he understood socialism. Yet others demonstrate how amenable Polanyi’s ideas are to further development. Last but not least, the introduction outlines Polanyi’s historical diagnosis as it emerges from these innovative contributions and argues that the stark choice he felt faced European societies, socialism or fascism, is once again before us as we face the groundswell of nationalist and far right forces.
Keywords: capitalism; contemporary relevance; fascism; socialism

Double movement, embeddedness and the transformation of the financial system - Galarza, Oscar Ugarteche (Karl Polanyi and twenty-first-century capitalism, 2020)
The chapter reviews aspects of the possible transformation of the financial system into a banking complex, that comprises both embedded Too Big to Fail (TBTF) financial institutions and disembedded ones. The transformation of the financial system into a two-tier banking complex is the result of the disconnection of the TBTF embedded institutions and the right size to fail disembedded financial institutions. The chapter revises the scope and consequences of this change on the monopolization of financial capitalism and international financial governance. It contains two sub-sections. The first reviews Polanyi’s concept of embeddedness/ disembeddedness and TBTF; the second reviews the concept of a complex. This chapter aims to use Polanyi’s concept of embeddedness and disembeddedness in order to understand how the category of TBTF financial institutions came into being through the double movement of market deregulation and social regulation. The concepts of embeddedness in social regulation and disembeddedness under market regulation permit an understanding of how, as the few TBTF financial institutions re-embedded themselves, becoming risk proof, the majority remained disembedded and subject to failures. We argue that, given this, the financial system may no longer be considered a system.
Keywords: disembeddedness; double movement; embeddedness; financial system; too big to fail

Debt, land and money: From Polanyi to the new economic archaeology - Hudson, Michael (Karl Polanyi and twenty-first-century capitalism, 2020)
Polanyi spoke of the commodification of money, and this chapter focuses on how interest-bearing debt became the major dynamic, also contributing to the commodification of land and labor. By the late third millennium BC the main way to obtain manual labor was to lend money and make debtors work off their debts as an antichretic interest charge. Personal debt became the lever for creditors to pry land out of the clan-based tenure system, mainly for sale under economic duress. Debtors who pledged their crop or land rights usually ended up forfeiting them. This alienation catalyzed the ‘commodification’ of land. By tracing these debt dynamics, the new economic archaeology is compatible with Polanyi’s intuitions and recognition that market relations are embedded in social relations, and extends his analysis in tracing how administered pricing and monetary valuations created the preconditions for market exchange. The earliest markets, credit and land tenure systems were regulated. Administered pricing was a precondition for creating weights, measures and price equivalencies to enable market exchange to evolve more flexibly.

Multilinear trajectories: Polanyi, The Great Transformation and the American exception - Lacher, Hannes (Karl Polanyi and twenty-first-century capitalism, 2020)
Karl Polanyi’s call, in The Great Transformation, for a re-embedding of markets, is widely understood to have come to fruition in the American New Deal and in the post-war order of ‘embedded liberalism’. Based on archival sources, this chapter shows that Polanyi’s political project was far more radical. Polanyi initially considered the New Deal a vital response to the problems of American capitalism, but one that would have little relevance to the problems and dynamics of European societies. There, he considered a socialist transformation both possible and necessary. But eventually, Polanyi realised that the US, far from remaining an exceptional outlier of ‘nineteenth-century civilisation’, was imposing its model on Britain and Europe. The internationalisation of the American New Deal in the Bretton Woods order marked the defeat of Polanyi’s political project.

Polanyi in space - Peck, Jamie (Karl Polanyi and twenty-first-century capitalism, 2020)
The chapter addresses the potential of Karl Polanyi’s contribution as a spatial theorist, or as an economic geographer in all but name. Although Polanyi did not identify as a spatial or geographical theorist as such, his work is rich with spatial insights and implications, notably as one of the original analysts of economic diversity. The chapter begins by contextualising Polanyi’s work in relation to the shifting locales and vantage points that shaped its production. It then turns to the question of the potential of Polanyi’s research programme (incomplete as it understandably was) for the conceptualisation and exploration of economic geographies. The goal here is to sketch some of the ways in which neoPolanyian approaches can be put to work in the service of geographically sensitive modes of economic inquiry, including those attuned to the ongoing diversity of economic formations and development trajectories, contemporary engagements with uneven spatial development, and the evaluation of (localised) economic experimentation. Polanyi’s programmatic project of ‘comparative economics’ was never completed during his own lifetime. There is much to be gained from resuming this project.

The reality of society - Rotstein, Abraham (Karl Polanyi and twenty-first-century capitalism, 2020)
In these remarkably stirring reflections, delivered at the 2014 conference from which most of the contributions to this volume emerge, the late Abe Rotstein, Polanyi’s student and collaborator, recalls the projected sequel to The Great Transformation, to be titled Freedom and Technology. Whereas the former was built on a social sciences approach using institutional analysis, the sequel was to follow the intention Hegel expressed in the words ‘Wir die religiöse Vorstellung in Gedanken fassen’ (We want to turn religious expression into philosophical thought). Polanyi took religion seriously – not its outer ceremonial trappings but the important truths that lay behind and beneath these beliefs and practices. The sequel was to trace humanity’s progression through three major revelations: the knowledge of death, the discovery of our inner life and conscience, and the realization of freedom amid our social obligations. This was the idea of ‘the reality of society’ around which the whole book was to be built. It was the precursor of our cherished civil freedoms and closely connected with Polanyi’s idea of freedom in a complex society; it is also deeply threatened in an age of state and corporate cyber surveillance.
Keywords: freedom; reality of society; technology

Polanyi’s democratic socialist vision: Piketty through the lens of Polanyi - Somers, Margaret R.; Block, Fred (Karl Polanyi and twenty-first-century capitalism, 2020)
This chapter brings Karl Polanyi into dialogue with Thomas Piketty, author of Capital in the Twenty-First Century. The dialogue is intended to make visible key aspects of Polanyi’s theoretical framework while also suggesting limitations in Piketty’s approach to political economy. Specifically, the authors use the concept of ‘predistribution’ – implicit in Polanyi – to critique Piketty’s emphasis on redistribution as the solution to growing wealth and income inequality. Predistribution conveys the idea that the initial market distribution of income is not natural but is shaped by the systematic exercise of political and economic power.

Fictitious ideas, social facts and the double movement: Polanyi’s framework in the age of neoliberalism - Thomasberger, Claus (Karl Polanyi and twenty-first-century capitalism, 2020)
In the last decades, Karl Polanyi has gained recognition as one of the most important social scientists of the twentieth century. His seminal book, The Great Transformation, is listed among twentieth- century classics. How can this book, written more than seventy-five years ago, be applied to the current conditions? In order to answer this question the chapter not only compares the civilization of the nineteenth century in Europe with our own epoch. It also reconstructs some of Polanyi’s most important insights, such as his critique of the liberal utopia (in its classical and neoliberal version), his interpretation of the double movement, his vision of the meaning of the industrial revolution, his understanding of the problem of freedom in a complex society and his idea of a necessary ‘reform of human consciousness’. The chapter closes with a discussion of the question of how Polanyi’s categories can be used fruitfully so as to throw light to the post-war era and our society today.
Keywords: Great Transformation, The (Book); double movement; freedom in a complex society; liberal utopia; social facts

The Euro as a Polity: Karl Polanyi in Frankfurt? - Thomasberger, Claus (Global Perspectives, 2020)
As factors of production, labor, money, and land play a role in economics that is rarely understood. The difficulty of deriving the contribution of the individual factor of production to the value of jointly produced final commodities (the famous “problem of imputation”) occupied generations of Austrian economists (Hayek 1984) and inspired Ludwig Mises to produce his 1920 article “Economic Calculation in the Socialist Commonwealth” (Mises 1935). Any attempt at rational socialist planning is utopian, Mises argued, because only price-making markets for the factors of production provide the information for economically rational decision-making. If the birthplace of neoliberalism was, as Slobodian (2018, p. 30) put it, Ludwig Mises’s office in the Vienna Chamber of Commerce, this article was its moment of birth.Karl Polanyi was one of the first to respond, doing so in the same journal in which Mises’s piece had been published, the Archiv für Sozialwissenschaften, long before Friedrich Hayek, Walter Lippmann, Lionel Robbins, and German ordoliberals such as Alexander Rüstow and Wilhelm Röpke intervened (Polanyi 2016, 2018b). In his contributions to what became the famous socialist accounting debate, Polanyi outlined his idea of a society’s “constitutional form … as a relationship of mutual recognition” (Polanyi 2018a, 54) based on direct cooperation between consumers and producers, as well as a functional democracy.Two decades later, Polanyi resumed this discourse with a more radical critique, making use of Mises’s argument for his own end (cf. Thomasberger 2020). Mises’s case for price making markets is no less utopian than the central planning model, he argued in The Great Transformation (TGT). The crucial point, Polanyi contended, is that the factors of production are fundamentally different from genuine commodities. Polanyi drew on a line of reasoning put forward by the sociologist Ferdinand Tönnies (2001, p. 81-82) and by Mises’s intimate enemy, the Austrian economist Friedrich Wieser (1927, p. 175-77), who was inclined toward Fabian socialist ideas. Given that the factors of production are not (and cannot be) produced for sale by private enterprises, the commodity form of labor, money, and land is fictitious.Polanyi’s category fictitious commodities is the pivot of Klein’s paper. This starting point allows him to go beyond the common interpretation of Polanyi’s work, which focuses on the dichotomy of market opening and social closure, and to address instead a more profound problem: the conflict between capitalism and democracy. Such a reading is indeed closer to the core of the Polanyi approach, which refers to a society that “transcends the self-regulating market by consciously subordinating it to a democratic society” (Polanyi 2001, 242). Not social protection, but democracy, is the alternative to the self-regulation of the market. Polanyi never believed that protection could achieve more than a temporary stabilization of market society. In fact, it is somewhat paradoxical that in the discussion about the contradictions of European integration, Polanyi is celebrated as a defender of societal closure, while he himself expressed the conviction that the protective measures “impaired the self-regulation of the market, disorganized industrial life … and finally disrupted the social organization based upon it” (Polanyi 2001, 4). From the point of view of the conflict between capitalism and democracy, the institutions that result from the attempt to commodify labor, money, and land are crucial because they are, as Klein puts it, the “point of entry of political power into the economic sphere” (Klein 2020, 11). Concerning the debate about the crisis of European integration, this is a rather unexplored terrain.In what follows, I will not discuss the question of whether the category fictitious commodities can be fruitfully linked to the idea of premodern modes of economic integration, a connection that Polanyi himself never established. Instead, I will concentrate on two issues that Klein’s paper raises without discussing them explicitly. The first question is: What if the creation of a self-regulating market system becomes the dominant political goal? What if, for example, the central bank is transformed into a market maker for money on political grounds? The second point seems to me even more important. Europe is not a nation. However, “in Polanyi’s schema, the self-regulating market was a national economic institution” (Polanyi-Levitt 2013, 89), which linked the “rest of the world” to England by a “golden straightjacket,” as Polanyi’s daughter, the development economist Kari Polanyi Levitt, remarked. In TGT even European colonialism plays only a marginal role. As a result, European integration after World War II raises issues that Polanyi did not discuss in depth. I will proceed in two steps: First, I will reconstruct some essential points of Polanyi’s analysis. Following this, I will pose the question of how to apply his analysis to Europe.From the point of view of a market system, the crux of the factors of production—or the fictitious commodities, as I shall hereinafter refer to them—is that, on the one hand, private enterprises must be enabled to buy labor, land, and money on a market. On the other hand, private companies are notcapable of producing and selling the fictitious commodities. The difficulty is obvious: In a market economy, enterprises depend on markets for the fictitious commodities, but such an economy is unable to produce them. This means that the market system depends on external forces. Certainly, this is also true for other institutions and social infrastructures that only the state can provide. However, the fictitious commodities are different in that they cannot be understood as part of the extra-economic framework. Labor, money, and land are economic factors; they are the condition sine qua non of the market system. No self-regulation is conceivable without including the fictitious commodities. What legal scholars with regard to the secular state call the Böckenförde dilemma in the case of fictitious commodities affects economic liberalism directly. The market system is unable to produce and reproduce itself spontaneously. The economic mechanism lives by prerequisites it cannot create. Social institutions are required to provide what for the functioning of a market system is indispensable. Only society can provide the commodities on which a market economy is based. Therefore, in a market society, the economy is not—and can never be—a functional machinery. “Laissez-faire economy was the product of deliberate State action,” as Polanyi (2001, p. 147) stated, summing up the nineteenth-century answer to the dilemma. The different institutions that coordinate economic activities are the outcome not of functional pressure but of a political struggle around the (de)commodification of the fictitious commodities. “Market economies are polities,” to paraphrase the felicitous title of a book edited by Christian Joerges, Bo Stråth, and Peter Wagner (2005).In other words, an ideal market society presupposes the political creation and regulation of particular social institutions whose purpose is to simulate market conditions. Unemployment insurance, health care, union legislation, central bank acts, land property rules, and environmental regulations are indispensable for transforming labor, money, and land into commodity-like entities. Here a conflict between the social nature of the task and its economic role arises. From the perspective of the market system, these institutions fulfill the function of market makers. However, from the viewpoint of society, they allow for various forms of political regulation and economic planning, taking into account the social needs of the different strata of society. It is this tension between their political roots and their economic function within the market system that puts these institutions at the center of the political struggle. Since law cannot ignore prevailing ideals, worldviews, and external expertise, it plays a contradictory role in this process, functioning as a vehicle for commodification and political regulation.In TGT Polanyi showed that from the beginning, law played a key role in the process of commodification. In England, three legal regulations were crucial:Even if a market society presupposes the commodification of all three fictitious commodities, for reasons of space I will concentrate on money. The crucial point is to understand that the nineteenth-century gold standard was primarily not an economic but a political system.In the first decades of the century, substantially inconvertible paper money circulated in England. The commercial banks—and their theoretical advocates, the so-called Currency School—pushed for the right to provide money according to the banks’ calculations. In contrast, the supporters of the Banking School argued that this would lead to the risk of an overissuance of notes. The essential feature of the banking system created by the abovementioned Peel’s Bank Act was to keep the supply of money artificially scarce by linking the amount of banknotes to the quantity of gold in the issuing department of the Bank of England (BoE). By law, political control and the discretionary influence of the government on money and banking were reduced to a minimum.Over the course of the century, the commodification of labor, money, and land in England set in motion a transformation on a global scale. Relying on bank money, the market system generated a previously unknown social and economic dynamic. In the last decades of the “long” nineteenth century, Polanyi (2001, p. 136) commented, “a new way of life spread over the planet with a claim to universality.” The international gold standard gave birth to a worldwide system, in which the constitutional regimes became almost the corollary of the gold standard.Here we can observe in outline two problems that we encounter again in Europe today: (1) Given the legislation that forced central banks to limit the supply of money, the international gold standard not only limited the British government’s room for maneuver, but it confined also, and often even more strictly, the policy space in the other countries. The open market for money and finance created international economic and political interdependencies, which reached deeply into society and undermined democratic aspirations. Social legislation, labor unions, and budgetary and monetary policy were forced to accept the priority of the external monetary stability even if this was in contradiction to national interests. (2) The variety of socioeconomic environments, institutional traditions, and sociopolitical objectives in different countries was negated. The gold standard forced the individual countries to adapt to the liberal economic model with its universal aspirations.The BoE functioned as the conductor of the global monetary orchestra. Polanyi introduced two categories to describe the international dependencies in this period: “anarchistic sovereignty and ‘justified’ intervention in the affairs of other countries” (Polanyi 2001, 261). On the one hand, sovereignty was “anarchistic” insofar as under the gold standard and the prevailing system of unregulated foreign trade, governments lacked any power with respect to international economic affairs. The treatment of trade as a relationship between private undertakings made effective international (political) economic cooperation between states impossible. On the other hand, interventions were “justified” whenever the budgets, finances, and currencies of debtor countries required control. Given the rigidities of the economic system, Polanyi underlined that “the peoples of the world were institutionally standardized to a degree unknown before” (Polanyi 2001, 261).At the same time, however, the inelasticity of the gold supply resulted in a deflationary bias that spread over the world. Even if central banks tried to introduce some doses of flexibility, the system required the adjustment of wages and prices to the current account balances, affecting both the opportunities for profit and the living conditions of large sections of the population. Such a rigid system could survive, Polanyi summarized, only as long as popular democracy was suppressed. Confronted withIn nineteenth-century England, the gold standard and popular democracy were irreconcilable. This explains why attempts to restore the former in the 1920s were bound to fail. Barry Eichengreen took up Polanyi’s point when he pointed out that after the First World War, “the spread of universal suffrage and … the consequent politicization of the policy environment … had destroyed the viability of the gold standard itself” (Polanyi 2001, 233–34). As long as prosperity prevailed, the conflict could be contained. Not so in crisis situations. The restored international gold standard collapsed in 1931.The European Monetary Union (EMU) is at the heart of current debates on the crisis of European integration. Whether Streeck (2014, p. 185) calls the EMU “a political mistake” or Habermas (2012, p. 3) criticizes the “construction flaw of a monetary union,” they share a focus on the Maastricht process. Obviously, this interpretation ignores the fact that the crisis also includes countries—among others the United Kingdom, Poland, and Hungary—that have never been part of the EMU.If we look at the crisis from Polanyi’s perspective, the focus shifts. Not the EMU but the Single European Act, signed in 1986, emerges as the turning point. The single market program was by no means the deregulatory exercise that the European Commission had presented it as being. It was about developing competition throughout the European Union, including markets for labor, land, and money. The novel feature of the program was that it aimed at creating cross-national markets for the fictitious commodities between democratically constituted countries. This is not to say that markets for genuine goods do not cause interdependencies; however, the political character of the process of commodification of the fictitious commodities produces interdependencies of a different quality. Economic, monetary, fiscal, income, and social policy decisions in one country affect directly all other countries participating in the single market. They create political interdependencies, which, if we take Habermas’s understanding that “democratic self-government means that the addressees of mandatory laws are at the same time their authors” (Habermas 2012, 14), is incompatible with national democracy.Why did Jacques Delors and the European Commission nevertheless argue for the creation of Europe-wide markets for the fictitious commodities? Did they underestimate the political costs? Or did they believe that the economic benefits outweighed the loss of political self-determination?It is important to keep in mind that the discussions within the economic discipline never led to the consensus that the European Commission assumed. David Ricardo (1817) had already argued that markets for production factors are by no means necessary in order to enjoy the advantages of the international division of labor. In the twentieth century, declared supporters of free trade such as Gottfried Haberler (1930) and Jagdish Bhagwati (1998) took the same line. Recently, an IMF Staff Paper evaluating empirical studies on the effects of financial globalization concluded that there is evidence not of direct economic gains but rather of political effects: “Our interpretation of the newer literature is that … financial openness can … impose discipline on macroeconomic policies” (Kose et al. 2009, 10). In Europe, the internal market program was met with strong approval by the neoliberal camp. It is reasonable to assume that with the single market, Europe made the political turnaround that the Anglo-Saxon world had already accomplished with Thatcher and Reagan.Be that as it may, the commodification of labor, land, and above all money changed the rules of the game.1 To remain within the context of monetary relations: Open financial markets transformed the European Monetary System (EMS) into an arrangement that came close to what McKinnon (1988) had defined as the “gold standard without gold.” Although the EMS was intended as a symmetrical arrangement, under the conditions of open financial markets the most hard-nosed national central bank, the Deutsche Bundesbank (DBB), assumed the role of a kind of European central bank. The monetary authorities of other European countries were forced to adapt. Recall that in autumn 1992, the conflicts that arose out of these political dependencies nearly put an end to European monetary integration. The different conditions—most European countries were in recession, while Germany was experiencing the unification boom—placed incompatible demands on monetary policy. In this conflict, the DBB acted not as a European but as a German central bank, raising interest rates to record levels. In September 1992, the system faltered. The Italian lira and the pound sterling were forced out of the exchange rate mechanism. Great Britain definitively turned its back on monetary integration, while in Italy a political earthquake shook the party-political landscape.Streeck (2014, p. 186) calls for “a new European monetary system” built on Keynes’s model of fixed but adjustable exchange rates. Now, Keynes was well aware of the fact that systems such as the Bretton Woods System (or the original EMS) are incompatible with transnational financial markets.2 They can function only as long as capital movements are politically controlled. The internal market program destroyed these conditions.Fatally, the Maastricht Treaty did not pursue the goal of reducing political interdependencies but was limited to replacing asymmetry with the all-encompassing dependence on a supranational, technocratic institution that is apparently separate from the political sphere. The German economist Horst Sievert (1993, p. 18) exposed the core idea of the EMU when he remarked, “What is decisive, is that in the monetary union the individual state must pay its debts with money that it cannot produce itself.”3 In the European type of monetary union, not the political authorities but technocrats and private financial institutions control the currency in which public debt is denominated. While in countries with their own currencies the government can turn to its central bank in a time of need, in the EMU, as we have seen in the case of Greece, state bankruptcy becomes a real threat.The financial and economic crisis has revealed the utopian character of the idea of imposing discipline through markets. To touch on just two aspects: (1) Since then, the socioeconomic heterogeneity between the countries has found new forms of expression. By creating long-term interest rate differentials, the crisis has spatially divided what was conceived as a single European capital market. Paradoxically, those countries most dependent on cheap credit are penalized by less favorable financing conditions. (2) If the demand for money and credit is insufficient, efforts to keep the money supply scarce lose their purpose. Neither the Public Sector Purchase Program (PSPP) adopted in 2015 nor the Pandemic Emergency Purchase Program (PEPP) can be derived from theoretical principles based on the commodity fiction of money. The coronavirus crisis is, as Peter Bofinger (2020) suggests, “the hour of Modern Monetary Theory”—an approach that until recently was marginalized by mainstream economics because it regards money not as a commodity but as a means of payment.To overcome the crisis of European integration, two alternatives are usually proposed: deepening integration, “an ever closer union,” or downscaling of integration, defending democracy on the nation-state level. More than seven decades ago, Polanyi already envisaged a third possibility: political cooperation between self-determining nations. Polanyi was in favor of (a) the international division of labor and (b) the liberty of the individual countries “to organize national life at will” (Polanyi 2001, 262). He was (c) aware that both could be achieved only if the commodification of labor, money, and land was restricted. His ideas were indeed aimed at politically controlled regional cooperation between countries that would maintain and develop their particular characteristics. In the final chapter of TGT, he highlighted:The link between the removal of the fictitious commodities from the market and the emergence of a variety of new societies is the crucial point. In another well-known essay published shortly after TGT, Polanyi outlined his idea of a global economic order by contrasting his concept of “regional planning” with that of “universal capitalism” (Polanyi 2018b). For Polanyi, a variety of human societies was not only a fact but also a normative value. It must suffice here to recall his last project, the magazine Co-Existence, which explicitly aimed at the strengthening of peaceful international cooperation.4From this perspective, the debate on the ECB cannot be limited to questions of Outright Monetary Transactions, negative interest rates, state financing, and price stability. The question of how the monetary authorities of a heterogeneous European Union can and should act has to go back to the root problem, the commodification of money. To bring Polanyi’s ideas to Frankfurt would mean at least:However, from the point of view of the commodity fiction, the erosion of the predominance of formal legal rules in the mid-1980s, the emergence of the “regulatory state,” the turn toward governance, and finally the spread of “executive managerialism” (Joerges and Weimer 2013) since the financial crisis appear as a series of functionally necessary adjustments to an originally incomplete regime. As long as this vision prevails, the tensions between increasingly technocratic rule and democratic control are likely to persist. In the light of Europe’s ever-growing diversity, a fundamental redesign of the project, including a reconceptualization of European law that overcomes the fiction of an apolitical integration process, is necessary and, indeed, overdue. Polanyi’s analysis can provide the economic and sociological premises for such an endeavor. However, his writings also show that, especially in the twentieth century, social transformations that would have been necessary proved impossible to implement. We should be prepared; the possibility of some kind of “fundamental shock” to the integration project cannot be ruled out.Claus Thomasberger is a sociologist and economist whose main fields of research are political philosophy, history of economic thought, international political economy, European integration and social ecological transformation. Until 2017, he was Professor of Economics and Foreign Economic Policy at the Berlin University of Applied Sciences. He has been a visiting Professor at the University of Knoxville, the Duke University, and the Vienna University of Economics and Business. He is a member of the Board of the Institute for Ecological Economy Research, Berlin, the International Karl Polanyi Society, Vienna, and of the Executive Committee of the Karl Polanyi Institute of Political Economy, Montreal. Among his publications are: Chronik der großen Transformation, Artikel und Aufsätze von Karl Polanyi 1920-1947 (3 vol.) (with M. Cangiani and K. Polanyi Levitt), 2002-2005; Der neoliberale Marktdiskurs (with W. Ötsch), 2009; Das neoliberale Credo, 2012; Auf der Suche nach dem Ökonomischen (with R. Lucas and R. Pfriem), 2018; Karl Polanyi’s Vision of a Socialist Transformation (with M. Brie), 2018; Karl Polanyi. Economy and Society. Selected Writings (with M. Cangiani), 2018.

The Contemporary Relevance of Karl Polanyi to Critical Social Enterprise Scholarship - Roy, Michael J.; Grant, Suzanne (Journal of Social Entrepreneurship, 2020)
The importance of the work of Karl Polanyi to social enterprise scholarship is often maintained. However, explanations as to how and why his ideas are so relevant to the field are still relatively scarce. In this essay, we argue that engaging with Polanyi’s work directly, and Polanyian scholarship more widely, can provide a deep understanding of the underlying assumptions within current social enterprise conceptualizations, and provide insights into how the relative positioning of market and society may be manipulated to maintain hegemonic positions. Three of Polanyi’s key concepts are considered and discussed in turn: the ‘substantive economy’, the notion of ‘embeddedness’, and his ‘double movement’ thesis. The contemporary relevance of each concept, and the implications for future research, are presented and discussed, with a view to providing a platform from which to pursue a reinvigorated, emancipatory critical research agenda.
Keywords: Polanyi; Social enterprise; critical research; critical social enterprise scholarship; double movement; economic sociology; embeddedness; social business; social enterprise; social innovation; substantive economy

Embedding the atom: Pro-neoliberal activism, Polanyi, and sites of acceptance in American uranium communities - Malin, Stephanie A.; Alexis-Martin, Becky (The Extractive Industries and Society, 2020)
In North America, uranium workers are fighting for their right to participate in a free-market system that provides them with small personal benefits. These workers experience powerlessness, instability, and unpredictability – or social dislocation – by living amidst capitalism’s polluted ecosystems, unstable economies, and disintegrating communities. However, they feel reliant on uranium for their livelihoods and strongly support the industry’s renewal and form sites of acceptance to support industry renewal. Here, we explore the phenomenon of pro-neoliberal activism emerging in communities that identify with uranium markets and that trust in corporate self-regulation, private transparency, and the perceived benefits of potential economic development. Polanyian theory helps us analyze these curious socio-environmental outcomes. While social movements might be ‘progressive,’ ‘regressive,’ or otherwise diverge, Polanyi consistently characterized double movement activists as protecting communities and ecosystems from unstable, self-regulating market systems. But here we see something different and ask: First, how does pro-neoliberal activism contribute to the embedding and institutionalization of neoliberal regimes in uranium mining communities? Second, what structural mechanisms precede and help to facilitate socio-cultural support for free markets and corporate self-regulation, as opposed to support for re-embedding markets in local, public social protections for the US uranium industry?
Keywords: double movement; environmental justice; pro-neoliberal activism; uranium

The surplus approach, Polanyi and institutions in economic anthropology and archaeology - Cesaratto, Sergio; Bucchianico, Stefano Di (Department of Economics University of Siena, 2020)
This paper was inspired long ago by Jared Diamond (1997), and in particular by his extensive use of the concept of economic surplus as the key to the development of civilization. Unfortunately, Diamond does not mention the origin of the concept in classical and pre-classical economics, nor does he pay much attention to debates in economic anthropology about the role of economic analysis in studying primitive and ancient economic formations. These debates were the subject of a recent book by Cedrini & Marchionatti (2017), who dispute the neoclassical “imperialist” attempt to occupy the territory of economic anthropology. The authors rely on the institutionalist background provided by Karl Polanyi and his school and by other anthropologists of similar inspiration. Polanyians, however, fail to complete their institutional analysis by anchoring it to the changing modes of generation and distribution of the economic surplus. Yet their emphasis on the need to introduce institutions from the beginning, when speaking of economic surplus, should be taken into consideration by the classical surplus approach
Keywords: Marx; Polanyi; Sraffa; economic anthropology; economic archaeology; surplus approach

Karl Polanyi and substantivism in economic development - Rodrigues, Waldecy; Santos, Nayara Silva Dos (Brazilian Journal of Political Economy, 2020)
ABSTRACT A reading of Karl Polanyi’s work gives us a broader and more plural view of the development process beyond the exclusively economic dimension. This scientific text aims to recover the theoretical contribution of Karl Polanyi and its contribution to the understanding of the development process from a plural and substantive conception of economy. The key lesson learned in this research is that regardless of a country’s economic system, one should pay attention to the existing institutional variety and complexity of its cultural and social mosaic. True development will only be achieved if it is structured with effective public policies in order to promote this heterogeneity to the maximum possible social welfare.
Keywords: Economic development; Karl Polanyi; plural economy

On the Nature of the Countermovement: A Response to Stuart et al.’s ‘Climate Change and the Polanyian Countermovement: Carbon Markets or Degrowth?’ - Carton, Wim (New Political Economy, 2020)
In a recent article for this journal, Stuart, D., Gunderson, R., and Petersen, B. [(2017). Climate change and the Polanyian counter-movement: carbon markets or degrowth? New political economy, 1–14. doi:10.1080/13563467.2017.1417364] discuss solutions to climate change in terms of Karl Polanyi’s concept of the double movement. They set up their argument as a critique of my own article on the topic to make the point that carbon markets do not constitute a genuine form of such countermovement. I’m sympathetic to the critique of carbon markets that the authors present, as well as their discussion of degrowth, which mirrors a by now extensive literature demonstrating the pitfalls respectively the necessity of these diametrically opposed approaches to the current socioecological crisis. However, in setting up their case the authors provide an overly optimistic reading of Polanyi that I believe misses a crucial part of his argument, a reading that at least partly explains our differences in opinion. This commentary offers a friendly critique of Stuart et al.’s use of Polanyi and clarifies the argument in my previous text that the authors take issue with.
Keywords: Polanyi; carbon markets; climate change; commodification; countermovement

Polanyi, Callon, and Amazon: Institutionalist, ANT, and DRAN Approaches to Platform Economies - Caliskan, Koray (Sociologica, 2020)
Drawing on a detailed analysis of Grabher and König’s study of platformization (Grabher & König, 2020), this essay develops a revision of Actor-Network Theory by proposing how a Device, Representation, Actor and Network or a DRAN Approach can be more helpful in making sense of platform economic processes. First, it locates the ways in which Grabher & König’s article approach platforms from an updated Polanyian perspective. Second, it elaborates on how the aforementioned article critiques static Polanyian perspectives while at the same time building a double tension by a) not being clear whether we observe "the platform economy" as an object or platform economization as a process, and b) not paying sufficient attention to how platforms that draw on intangible materialities move beyond being mere marketization relations. Third, it presents how to address these tensions by drawing on novel theoretical advances of DRAN Approaches and fresh empirical research concerning platform economies, located at the intersection between computer science and social sciences. Proposing a possibility to integrate historical and contemporary studies of economic processes, the essay ends by elaborating on how Grabher & König’s article has a potential to enable a multi-perspective dynamic research strategy in making sense of not only the contemporary working of platforms, but their historical and socio-technical condition of possibility.
Keywords: CALLON, Michel; Platform economy; Polanyi; actor-network theory; platform

Understanding the (Re-)regulation of Private Renting in England: Karl Polanyi, the Rogue Landlord, the Responsible Tenant and the Decent Home - Carr, Helen; Alcock, Rowan (Contract law and the legislature: Autonomy, expectations, and the making of legal doctrine, 2020)

Karl Polanyi and Twenty-first-century Capitalism - Desai, Radhika; Levitt, Kari Polanyi (Manchester University Press, 2020)
As far right movements, social disintegration and international conflict emerge from the decay of the neoliberal order, Karl Polanyi's warnings against the unbridled domination of markets, is ever more relevant. The essays in Karl Polanyi for the 21st Century extend the boundaries of our understanding of Polanyi's life and work. They will interest Polanyi scholars and all interested in socialism and our future after neoliberalism. One asks whether, following Keynes and Hayek, Polanyi's ideas will shape the twenty-first century. Some clarify, for the meaning of money as a fictitious commodity. Others resolve difficulties in understanding the building blocks of Polanyi's thought: fictitious commodities, the double movement, the United States' exceptional development, the reality of society, and socialism as freedom in a complex society. And yes others explore how Polanyi sheds light on income inequality, world systems theory, comparative political economy.
Keywords: capitalism; double movement; neoliberalism; reality of society; socialism

Ecology, democracy, and COVID-19: Rereading and radicalizing Karl Polanyi - Duzgun, Eren (Ecology, democracy, and COVID-19, 2020)
This chapter argues that Karl Polanyi’s economic sociology offers foundational concepts for a radical analysis of the social and ecological conditions that have caused the coronavirus pandemic. Furthermore, it shows that Polanyi’s work, often claimed for social democracy, has the potential to provide much more radical insights into the question as to how to “re-embed” our economies, thereby leading to a fundamental rethinking about the ways in which the present crisis can be overcome.
Keywords: COVID-19

The Specter of the 1930s in Asian Nation-Building: Global Fascism, Colonial Biopolitics, and the Origins of Modern Asia - Lee, Alex Taek-Gwang (Back to the ‘30s? : Recurring Crises of Capitalism, Liberalism, and Democracy, 2020)
An analysis of the connection between fascism and biopolitics in modernizing East Asia reveals that fascism served as colonial biopolitics, and was not historically specificity to Europe, though the rise of fascism was central to European colonialism and its technology of governance. As the last stage of capitalism, imperialism came with an expansion of social engineering in colonial countries, forcing colonized peoples to be “civilized.” I challenge the understanding of European fascism, arguing that fascism is inseparable from colonial biopolitics by analyzing non-European experiences in the 1930s. East Asia was then a site in which fascism, premised on building a utopian nation-state, played a pivotal role in encouraging people to insist upon political and economic autonomy in order to compete with Europe. The Manchurian Empire (滿州帝國) was an attempt to realize this utopian idea of fascism. Finally, I argue that these fascist experiences remain influential in the region and constitute a mirror image of European modernity.
Keywords: Japanese Fascism and Imperialism; Japanese colonialism; Manchukuo, history and politics; biopolitics of colonialism; fascism; nationalism and nation-building in East Asia

State Formation, Habitus, and National Character: Elias, Bourdieu, Polanyi, and Gellner and the Case of Asylum Seekers in Ireland - Loyal, Steven; Quilley, Stephen (Historical Social Research, 2020)
Synthesizing material derived from Norbert Elias, Pierre Bourdieu, Karl Polanyi, Max Weber, Benedict Anderson and Ernest Gellner, in Part I the concept of “national character” is delineated as a special case of “habitus” relating to the socio-spatial scale of the nation state. In relation to problems of state-formation, national character is shown to be a figurational and co-developmental function of the system of nation-states in which patterns of mutual identification and “imagined community” involve both the coercive codification and internalization of particular national narratives and origin myths which define “people like us” in terms of a symbolic family; and also, in relation to competing nation-states, the projection and internalization of national group charisma and shame. In Part II, these ideas are applied to the pattern of state formation in Ireland and the recent history of the reception, cultural accommodation, and treatment of asylum seekers.
Keywords: BOURDIEU, Pierre, 1930-2002; ELIAS, Norbert; Ireland; Irishman; Kultur; Sozialpsychologie; Staatenbildung; culture; figuration; habits; habitus; nation; national identity; national stereotype; nationale Identität; nationales Stereotyp; social psychology; state formation

Where are markets? - Peck, Jamie (Market/Place: Exploring Spaces of Exchange, 2020)
The goal of this chapter is to prepare the ground for theorizing the diversity and spatiality of markets, (necessarily) dealing with, but seeking to move concertedly beyond, the restrictive optic of the orthodox model. It seeks to do so by way of three steps. The following section opens up some preliminary questions about the place of markets and their actually existing historical geography. Next, the chapter turns to the challenge of decentring the market, of moving beyond the idea that the market properly and eternally belongs at the centre of the economic universe. What is the scope for understanding “real markets”, both conceptually and empirically, without recourse to the idealized model of the “pure” market, and all its downstream distortions? Finally, the chapter addresses the question of alternative “mappings” of markets, taking some cues from the work of Karl Polanyi, but urging a more thoroughgoing reconstruction. The chapter’s conclusion acknowledges that the “where?” of markets remains a demanding theoretical question, such that what follows serves to inform some different points of departure, not the destination itself. New answers to this “where?” question, though properly a matter for what Polanyi characterizes as the “substantivist” investigation of real-world market formation, re-formation and transformation, ought to recognize, inter alia: first, the relational character of markets, which are codependent on non-market modes of coordination and regulation; second, their “instituted” form, necessary in function but variable in practice; and not least, third, their always out-of-equilibrium processual dynamics and contradictions.
Keywords: markets; space

Introduction : exploring markets - Peck, Jamie; Berndt, Christian; Rantisi, Norma (Market/Place: Exploring Spaces of Exchange, 2020)
The origin of the present volume was an invitational workshop focused on questions of the spatiality and diversity of markets, held at the Karl Polanyi Institute of Political Economy in Montreal in the summer of 2017. This was an apt meeting place in a more than literal sense. Although many of those in attendance did not subscribe explicitly to a Polanyian worldview or mode of analysis, most had engaged with Polanyi’s work in different ways. Some had made extensive contributions to neo-Polanyian scholarship, while others were more closely affiliated to radical political economy, performativity approaches or poststructuralism. In this context, more pertinent were a series of broadly aligned sympathies with what might be characterized as Polanyian dispositions, including: shared recognition of the importance of respectful, constructive and non-dogmatic exchange across an interdisciplinary range of heterodox and critical positions; overlapping concerns with the potential of empirically engaged and “substantivist” investigation (to borrow the Polanyian terminology), not just in testing and tweaking extant theories but in the construction of new insights, understandings and socio-political visions; and mutual commitments to humane, emancipatory and sustainable modes of socio-economic and ecological development.
Keywords: Karl Polanyi Institute of Political Economy; economic geography; markets

The utopian character of the counter-movements : reading Karl Polanyi in the twenty-first century - Rondelez, Pieter (13th Global Studies Conference : Globalization and Social Movements : Familiar Patterns, New Constellations?, 2020)
In the introduction of the 2001 edition of The Great Transformation, Fred Block argues that we all have much to learn from the insights of Karl Polanyi. Relying on Polanyi’s arguments in the Great Transformation is not only useful in order to understand the history of market liberalism, but also for the contemporary debate on globalization and its contestation. The work of Karl Polanyi is inspiring a lot of academics nowadays who are studying the global uprisings since 2008. Some academics – like Block - argue that neoliberals embrace the same utopian visions of their predecessors which lead to counter-movements that are resisting marketization processes and its political and economic consequences. Relying on Polanyi’s work, I point to a danger of interpreting the current neoliberal order as a similar trend towards marketization as in the period that Polanyi is dealing with in his book. Misinterpreting the current marketization project raises questions not only about the feasibility of re-embedding the economy back into society, but also about the desirability of disembedding society from the economy. In concrete, I argue that the utopian character shifted from the marketization project to the counter-movements that are trying to resist and change it. This also raises questions about the role of social scientists in (studying) the process of social change in the twenty-first century.
Keywords: contemporary relevance; countermovement; globalization; marketization; utopia

The Moral Economy of the Capitalist Crowd: Utopianism, the Reality of Society, and the Market as a Morally Instituted Process in Karl Polanyi’s The Great Transformation - Somers, Margaret R. (Humanity: An International Journal of Human Rights, Humanitarianism, and Development, 2020)
In an age of egregious inequality and rising authoritarian, many call for a new “moral economy” and turn to Karl Polanyi’s The Great Transformation for inspiration. Yet Polanyi’s great insight is that those who cannot reckon with the moral economy of “market justice”—the claim that market outcomes, however unequal, are morally just—fail to understand the power of capitalism. Justified by its original claim to rest on natural science, market justice laid the predicate for democracy as mortal threat. Polanyi reveals market justice as based not on natural law but on predistributive political power, and builds his democratic socialist vision on the “reality of society.”
Keywords: market justice; moral economy